Clinical Course of Acute Kidney Injury in Elderly Individuals Above 80 Years - Isabell Funk; Eric Seibert; Silke Markau; Matthias Girndt (Karger Publishers, 2016)
Background/Aims: Aging is associated with renal function decline and elderly patients are more vulnerable to acute kidney injury (AKI). The causes and prognosis of AKI according to new KDIGO definition that broadened the diagnosis and included more patients without dialysis dependence have not yet been compared between younger and elderly patients. Methods: In a retrospective analysis all patients with AKI admitted to a tertiary care Nephrology department (N=424) were included. Individuals were stratified by age (≤80 years, >80 years). Primary end-point was death or dialysis dependence at hospital discharge, secondary analyses addressed the need for dialysis, creatinine at discharge, mortality, and length of stay. Results: The distribution of AKI causes was different between the age groups. Circulatory AKI was the most important cause in both groups; however, septic or toxic AKI contributed relevantly in younger patients. Nevertheless, the number of patients reaching the primary end-point was similar (younger, 20.4%; older, 18.0%; OR 1.17, 95%CI, 0.703-1.948). While mortality tended to be higher in the older population, none of the secondary analyses indicated worse outcome for the older patients. Conclusion: The prognosis of AKI in elderly patients is not necessarily worse than in middle aged individuals. Nevertheless, older patients may be particularly vulnerable to circulatory or ischemic insults of the kidneys.